Digitalisasi dan Tantangan Kedaulatan Hukum Nasional: Studi tentang Pergeseran Otoritas dari Negara ke Entitas Digital Global - Gilang Rizki Aji Putra (BULETIN ADALAH, 2020)
Digitalization has blurred the geographical boundaries underpinning state legal sovereignty. This article analyzes how digitalization erodes national legal sovereignty through three mechanisms: extraterritorial foreign regulation, dominance of digital platforms as quasi-sovereign actors, and reliance on global technical standards. Using normative legal research with conceptual and statutory approaches, the study finds that Indonesia’s legal sovereignty is continuously negotiated with market forces and transnational regulatory regimes. The Brussels Effect and corporate-controlled code architectures limit national legislation. Maintaining sovereignty requires shifting toward functional sovereignty focused on controlling critical infrastructure and data.  Keywords: Legal Sovereignty, Digitalization, Extraterritoriality, Digital Platforms, Data Sovereignty